Essential medical terminology : your lifeboat in the sea of terms - Honč, Petr; Přívratská, Jana; Hellerová, Kristina (Charles University, Karolinum Press, 2022)
The university textbook focuses on basic medical terminology in Latin and in English.
Keywords: lékařství; angličtina; Terminology as Topic; lingvistika; lingvistika, lékařská terminologie; latina; Linguistics; terminologie jako téma